Clinical assessment of Persian translation of Fullerton Advanced Balance Scale in community-dwelling older adults. Issue 4 (13th February 2020) - Azad, Akram; Sabet, Azar; Taghizadeh, Ghorban; Mohammadi-Nezhad, Tayyebe
Abstract: Background: Aging increases the probability of falling. Fullerton Advanced Balance Scale is developed to assess balance and the purpose of this study is examination of the validity and reliability of Persian version of the scale in Iranian community-dwelling older adults. Methods: The "forward-backward" procedure was applied for translation. Content validity was calculated by agreement of experts. For evaluation concurrent criterion validity, correlation of Fullerton Advanced Balance Scale with Berg Balance Scale, Timed Up and Go Test, and Functional Reach Test was measured. Retrospective self-report of fall was applied for considering predictive criterion validity. For assessment of construct validity, exploratory and confirmatory factor analyses were performed. Intraclass correlation coefficient (ICC), Kappa Coefficient, standard error of measurement (SEM), and Cronbach's alpha were used to assess reliability. Results: Content validity was acceptable (0.8–1). Concurrent criterion validity was calculated moderate-good (Fullerton Advanced Balance Scale with Berg Balance Scale, Berg Balance Scale static, and Berg Balance Scale dynamic: 0.65, 0.68, and 0.44. Fullerton Advanced Balance Scale with Timed Up and Go Test and Functional Reach Test: −0.77 and 0.6, respectively). Fullerton Advanced Balance Scale had an inverse linear relationship with fall probability. In factor analysis, two factors were extracted. ICC (95% confidence interval) for both test–retest and inter-rater reliability (0.92 and 0.72–1) was excellent (0.97 and 0.92) and Kappa for both test–retest and inter-rater reliability was good. SEM at test–retest reliability (0.17) and inter-rater reliability (1.25) was good. Excellent homogeneity was got (Cronbach's alpha: 0.84). Conclusions: The Persian version of the Fullerton Advanced Balance Scale is a reliable and valid tool for measuring balance in Iranian community-dwelling older adults. Implications for rehabilitation: Existence of a scale that measures the balance in high-performance individuals, as well as small changes in balance is essential in rehabilitation. Obtaining the validity and reliability of the Fullerton Advanced Balance Scale, which has the mentioned characteristics in older adults, enhances rehabilitation interventions in these population.